Experimental research on creep characteristics and failure mechanism of mining roadway in nearly vertical coal seams - Bai, Peng; Li, Zhiyong; Yu, Cong; Liu, Enqiang; Gao, Hui; Xie, Yuanman; Yan, Zhongming (Frontiers in Earth Science, 2024)
Nearly vertical coal seams present a significant challenge for the coal mining industry due to their difficult accessibility. However, these seams account for a substantial proportion of the world's coal reserves. Therefore, it is vital to conduct research on disaster control techniques for safe mining of these seams. The research team used experimental research, theoretical analysis, and numerical calculation methods to investigate the creep characteristics and failure mechanisms of layered sandstone roadway in nearly vertical coal seam. These findings revealed that the maximum moment and concentrated stress of the sandstone located on the side of the roadway roof was positioned in the middle of the nearly vertical structure, making it more susceptible to transverse shear failure. On the other hand, the nearly vertical structure on the floor side was prone to shear slip failure initiated from the bottom of the structure. This led to the asymmetric instability of the roadway. The practical implications of this research are significant for the safe mining of nearly vertical coal seams. The results could help inform the development of disaster control techniques.